Carlos Alberto Pinto Fonseca: um estudo de suas composições para cordas - Luiza Gaspar Anastácio (2014)
This research consists of a study of the works for strings written by the Brazilian composer Carlos Alberto Pinto Fonseca, aiming to present them to the music community and situate them among his whole work, on which the predominant compositions were written for choir. The research presents analysis of his three works originally composed for strings Estrutura nº1 para violino e piano (1971), Alma de Nossa Terra (1974) and Fuga para Quarteto de Cordas (1977) and observations about transcriptions and unfinished works of the composer. The research includes scores, a performance edition for the violin part of Estrutura nº1 para violino e piano and the manuscripts found during the research.